Clinical epidemiological characterization of COVID-19 sequelae in adults recovered from a hospital in Huancayo - Mauricio Trelles, Paola Beatriz (2022)
Objective. To describe the clinical and epidemiological characteristics ofthe persistence of post-COVID-19 symptoms in the population attended ata hospital in the city of Huancayo, Tambo district (Peru). Methods. The studyhad a cross-sectional, retrospective and observational quantitative approach. The population consisted of 110 clinical histories of adults recovered from the COVID-19, with a sample of 88 patients selected by non-probabilistic sampling. The instrument used was the retrospective data collection form using the patients' clinical histories, and for the analysis of the data, afrequency analysis was performed. Results. The clinical cases of patients with sequelae of COVID-19 were analyzed and it was found that the age group36-59 was the most affected, where the female sex predominated. The mostfrequent symptoms were fatigue, followed by shortness of breath, chest pain and cough. The clinical characteristics were that all patients presented mainsymptoms such as fatigue, cough and chest pain. Treatment was based ondexamethasone, azithromycin and amoxicillin with an average hospital stay of 2-4 weeks. Conclusions. The main characteristics of the patients with postCOVID-19 sequelae were: female, adults between 36 and 59 years of age, mostly with a history of diabetes.